Prevalence, pattern and clinical relevance of ultrasound indices of congestion in outpatients with heart failure. (22nd January 2019) - Pellicori, Pierpaolo; Shah, Parin; Cuthbert, Joe; Urbinati, Alessia; Zhang, Jufen; Kallvikbacka‐Bennett, Anna; Clark, Andrew L.; Cleland, John G.F.
Abstract : Aims: Even if treatment controls symptoms, patients with heart failure may still be congested. We aimed at assessing the prevalence and clinical relevance of congestion in outpatients with chronic heart failure. Methods and results: We recorded clinical and ultrasound [lung B‐lines; inferior vena cava (IVC) diameter; internal jugular vein diameter before and after a Valsalva manoeuvre (JVD ratio)] features of congestion in heart failure patients during a routine check‐up. Of 342 patients who attended, predominantly in New York Heart Association class I or II ( n  = 257; 75%), 242 (71%) had at least one feature of congestion, either clinical ( n  = 139; 41%) or by ultrasound ( n  = 199; 58%). Amongst patients ( n  = 203, 59%) clinically free of congestion, 31 (15%) had ≥ 14 B‐lines, 57 (29%) had a dilated IVC (> 2.0 cm), 38 (20%) had an abnormal JVD ratio (< 4), 87 (43%) had at least one of these, and 27 (13%) had two or more. During a median follow‐up of 234 (interquartile range 136–351) days, 60 patients (18%) died or were hospitalized for heart failure. In univariable analysis, each clinical and ultrasound measure of congestion was associated with increased risk but, in multivariable models, only higher N‐terminal pro‐B‐type natriuretic peptide and IVC, and lower JVD ratio, were associated with the composite outcome. Conclusions: Many patients with chronic heart failure with few symptoms have objective evidence of congestion and this is associated with an adverse prognosis. Whether using these measures of congestion to guide management improves outcomes requires investigation.